Effectiveness of Ring Card as a Promotive Effort For Mothers Under Two Years in Stunting Prevention - Nanik Cahyati; Mega Dewi Lestari (Jurnal Kesehatan Prima, 2022)
One of the nutritional issues in toddlers who need attention both at home and abroad at this time is Indonesia is stunting. Included in the third country with the highest prevalence in Southeast Asia. In  2017  the number of toddlers in the world who experienced stunting was as much as 22.2% or about 150.8 million. Stunting is a very short state of the body in accordance with the standard WHO-MGRS standard with another definition is disruption of physical growth and brain development, which can affectability and achievement, productivity, and creativity in the productive age. One of the prevention carried out by The government so that Indonesian children can grow and develop optimally, accompanied by emotional, social, and physical abilities that are ready to learn, innovate and compete at the global level. One of the efforts that can be done to prevent stunting is to provide information to the mother or family through interesting health media.  Ring Card is one of the easy-to-carry media, with the use of interesting colors and images containing applicable material so that it is expected that the knowledge, attitude, and skills of mothers can be improved. Research Methods used that are experimental quasi with pre-post design in 30 toddlers mothers.  In The Practice of Independent Midwives of West Bandung Regency, the data analysis test used is the Wilcoxon test, Paired T-Test.  The results obtained are: there is a difference in the increase in pre-test 10.50 to 15.00 with a value of p 0.000 (p<0.05), while the attitude variable is obtained that there is an increase in the mean value from 22.31 to 25.71, with a value of p 0.000 (p<0.05). and in skill variables, there is an increase in the median from 85.00 to 100.00, with a value of p 0.000 (p<0.05). The conclusion of this study the use of ring cards proved effective as a promotive effort in the toddler’s mother in the prevention of stunting.